Question
Factorise completely: 1. \( t x-t y+r x-r y \) 2. \( b y-a x+b x-a y \) 3. \( 3 a^{2}-a x+6 a b-2 b x \) 4. \( x^{3}+3 x^{2}-x-3 \) 5. \( 2 a-1-2 a b+b \) 6. \( 6 x^{2}-a y-2 a x+3 x y \) 7. \( 4 a^{2}-4 b^{2}-b^{3}+a^{2} b \) 8. \( 6 x^{2}-x^{5}-6+x^{3} \) 9. \( x^{4}-x^{2}-x^{2} y^{2}+y^{2} \) 10. \( x^{3}+y^{3}+x+y \)
Ask by Jimenez Munoz. in South Africa
Feb 04,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
1. \( t x - t y + r x - r y = (t + r)(x - y) \)
2. \( b y - a x + b x - a y = (b - a)(x + y) \)
3. \( 3 a^{2} - a x + 6 a b - 2 b x = (3a - x)(a + 2b) \)
4. \( x^{3} + 3x^{2} - x - 3 = (x + 3)(x + 1)(x - 1) \)
5. \( 2 a - 1 - 2 a b + b = (2a - 1)(1 - b) \)
6. \( 6 x^{2} - a y - 2 a x + 3 x y = (3x - a)(2x + y) \)
7. \( 4 a^{2} - 4 b^{2} - b^{3} + a^{2} b = (b + 4)(a - b)(a + b) \)
8. \( 6 x^{2} - x^{5} - 6 + x^{3} = - (x - 1)(x + 1)(x^3 - 6) \)
9. \( x^{4} - x^{2} - x^{2} y^{2} + y^{2} = (x - 1)(x + 1)(x - y)(x + y) \)
10. \( x^{3} + y^{3} + x + y = (x + y)(x^{2} - xy + y^{2} + 1) \)
Solution
Here are the complete factorizations for each of the given expressions:
1. **\( t x - t y + r x - r y \)**
Factor by grouping:
\[
t(x - y) + r(x - y) = (t + r)(x - y)
\]
**Factorized Form:** \((t + r)(x - y)\)
2. **\( b y - a x + b x - a y \)**
Rearrange and factor:
\[
b(x + y) - a(x + y) = (b - a)(x + y)
\]
**Factorized Form:** \((b - a)(x + y)\)
3. **\( 3 a^{2} - a x + 6 a b - 2 b x \)**
Factor by grouping:
\[
3a(a + 2b) - x(a + 2b) = (a + 2b)(3a - x)
\]
**Factorized Form:** \((3a - x)(a + 2b)\)
4. **\( x^{3} + 3x^{2} - x - 3 \)**
Factor by grouping:
\[
x^{2}(x + 3) - 1(x + 3) = (x + 3)(x^{2} - 1) = (x + 3)(x + 1)(x - 1)
\]
**Factorized Form:** \((x + 3)(x + 1)(x - 1)\)
5. **\( 2 a - 1 - 2 a b + b \)**
Rearrange and factor:
\[
(2a - 2ab) + (b - 1) = 2a(1 - b) + 1(b - 1) = (2a - 1)(1 - b)
\]
**Factorized Form:** \((2a - 1)(1 - b)\)
6. **\( 6 x^{2} - a y - 2 a x + 3 x y \)**
Factor by grouping:
\[
2x(3x - a) + y(3x - a) = (3x - a)(2x + y)
\]
**Factorized Form:** \((3x - a)(2x + y)\)
7. **\( 4 a^{2} - 4 b^{2} - b^{3} + a^{2} b \)**
Factor by grouping:
\[
(4a^{2} + a^{2}b) - (4b^{2} + b^{3}) = a^{2}(4 + b) - b^{2}(4 + b) = (4 + b)(a^{2} - b^{2}) = (4 + b)(a - b)(a + b)
\]
**Factorized Form:** \((b + 4)(a - b)(a + b)\)
8. **\( 6 x^{2} - x^{5} - 6 + x^{3} \)**
Rearrange and factor:
\[
-x^{5} + x^{3} + 6x^{2} - 6 = -(x^5 - x^3 - 6x^2 + 6)
\]
Factor \(x^5 - x^3 - 6x^2 + 6\) by finding roots:
\[
x^5 - x^3 - 6x^2 + 6 = (x - 1)(x + 1)(x^3 - 6)
\]
**Factorized Form:** \(- (x - 1)(x + 1)(x^3 - 6)\)
9. **\( x^{4} - x^{2} - x^{2} y^{2} + y^{2} \)**
Factor by grouping:
\[
x^{4} - x^{2} y^{2} - x^{2} + y^{2} = (x^{2} - 1)(x^{2} - y^{2}) = (x - 1)(x + 1)(x - y)(x + y)
\]
**Factorized Form:** \((x - 1)(x + 1)(x - y)(x + y)\)
10. **\( x^{3} + y^{3} + x + y \)**
Factor by grouping:
\[
x^{3} + y^{3} + x + y = (x + y)(x^{2} - xy + y^{2}) + (x + y) = (x + y)(x^{2} - xy + y^{2} + 1)
\]
**Factorized Form:** \((x + y)(x^{2} - xy + y^{2} + 1)\)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Mind Expander
Sure! Here are the completely factorised forms: 1. **\( t (x - y) + r (x - y) = (t + r)(x - y) \)** 2. **\( (b - a)(x - y) \)** 3. **\( (3a - 2b)(a + 3) - x(a - 6) = (3a - 2b - x)(a + 3) \)** 4. **\( (x + 3)(x^2 - x - 1) \)** 5. **\( (2a + b - 1) \)** 6. **\( 3x (2x - a + y) - a y \)** 7. **\( (4a^2 - b^3) - 4b^2 = (2a - b)(2a + b) \)** 8. **\( x^2(6 - x^3 + x) = x^2(6 + x - x^3) \)** 9. **\( (x^2 - y^2)(x^2 + 1) = (x - y)(x + y)(x^2 + 1) \)** 10. **\( (x + y)(x^2 - xy + y^2 + 1) \)** Happy factoring!